ANALYZING THE ROLE OF SERVICE QUALITY ON CUSTOMER SATISFACTION IN SHAPING CUSTOMER LOYALTY: CASE STUDY OF SOLARIA MALL KELAPA GADING - Natalie, Gabriella; Belgiawan, Prawira Fajarindra (Journal of Business and Management, 2018)
Abstract.Competition between restaurants has given too many choices for consumers of the products provided as the food industry grows. One of the most fundamental factors to survive in fierce competition is the service provided to the customers. The service provided to the customers leads to customer satisfaction, and further leads to customer loyalty. So that customer loyalty could not be separated from various factors such as perceived service quality and customer satisfaction. This study examines the effect of service quality on customer satisfaction in forming customer loyalty in Solaria Mall Kelapa Gading. Respondents for this research are 100 consumers in Solaria Mall Kelapa Gading, Jakarta. Sampling method used is non-probability sampling with convenience sampling technique. The sampling result is processed by using path analysis technique. According to this study, service quality has a significant influence on customer satisfaction and customer satisfaction also has a significant influence on customer loyalty. Customer satisfaction also plays a mediation role between service quality and customer loyalty.Keyword: service quality, customer satisfaction, customer loyalty.Â Â Â